An annealing study of the R1 EPR centre (the nearest-neighbour di-<100>-split self-interstitial) in diamond - Twitchen, D; Newton, M; Baker, J; Anthony, T; Banholzer, W (2001)
Results are reported of both isochronal and isothermal annealing studies of the R1 EPR centre (known to be a pair of parallel nearest-neighbouring <100>-split self-interstitials) produced by 2 MeV electron irradiation of synthetic type IIa diamonds of very low defect concentration before irradiation. The annealing out of R1 is not associated with any overall change in the concentration of isolated vacancies or interstitials. The isothermal decay corresponds to a first-order process with a rate constant conforming to an Arrhenius relationship with activation energy 0.6(1) eV and an unusually low attempt frequency. That the activation energy is much lower than the migration energy of isolated interstitials (1.68(15) eV) is taken to indicate that it corresponds to a combination of the energy required to excite R1 into an S = 0 state and that required to translate one of the split interstitials over the potential barrier into the next lattice site. This process may be linked to an associated rise in the concentration of the 3H (2.462 eV) optical defect; but the precise relationship between the diamagnetic site formed by the decay of R1 and the 3H optical centre is not revealed by this study.